The Revival Of Celadon Glaze Of The Song Dynasty: An Experimental Exploration And Its Contemporary Application In Ceramic Design - Bin, Dai (2023)
The main goal of this study is to create a new celadon formula, in line with contemporary industrial production methods, through the analysis of samples from the Song Dynasty celadon. The study has utilized a combination of synthetic materials and high-purity industrial materials to mimic Song Dynasty celadon samples in both oxidizing and reducing atmospheres.